Does Gender Diversity Improve Financial Firm's Performance? New Evidence using Two-Stage Least Squares Estimation and Instrument Variables - Vo, Hong Duc (University of Economics Ho Chi Minh City, 2023)
In this paper we examine whether a positive relationship exists between board’s gender diversity and financial firm’s performance. The study is conducted on a sample of US firms which provides us with as many as possible observations for various econometric techniques. Findings from our two-stage least squares estimation using the fraction of male directors on at least two boards as an instrumental variable show that higher proportions of female directors adversely affect firm value. We further test whether board diversity improves the performance of firms with otherwise weak governance. However, the results are not statistically significant. We also extend our model to the committee level, and our results show that increased representation of women in Audit and Nomination committees are likely to deteriorate the performance of the company as measured using Tobin’s q. The implication for Vietnam is that while a representation of female directors in a board of directors may improve firm’s performance as findings from Vo and Phan (2013) indicate, increasing a number of female directors may not be the case to improve financial firm’s performance.